The Impact of Domestic Violence on Women in the Drama "Behind Closed Doors" by Janet Shaw 2005 - Novita, Devi; Al-Hafizh, Muhd. (English Language and Literature, 2023)
This research is an analysis of the drama "behind closed doors" by Janet Shaw (2005).  In this study, the author aims to reveal the issue of the impact of domestic violence on women faced by Harriet and Pearl's characters as wives who experience domestic violence by their husbands.  In this analysis, there are two impacts of domestic violence.  The first is abnormal behavior such as having an imaginary friend / a fantasy man as a way to survive in the household. Having an imaginary friend they can express all the desires they cannot get from a husband.  The next abnormal behavior found is normalizing violence by blaming herself and feeling worthy of being given violence by her husband because she is already in a case of depression. The second is the impact of physical injuries and bruises due to domestic violence received by women. This analysis uses the concept of "abnormal behaviors" which is a branch of psychology proposed by Sigmund Freud and supported by several other experts. The use of concepts based on the context of the drama and interpretation of the text.  In this analysis, the elements of drama that help reveal the impact of domestic violence are stage direction and dialogue.